The multifaceted therapeutical role of low‐density lipoprotein receptor family in high‐grade glioma - Elisa Mastrantuono; Matilde Ghibaudi; Diana Matias; Giuseppe Battaglia (Molecular Oncology)
The diverse roles of the low‐density lipoprotein receptor family (LDLR) have been associated with many processes critical to maintaining central nervous system (CNS) health and contributing to neurological diseases or cancer. In this review, we provide a comprehensive understanding of the LDLR's involvement in common brain tumors, specifically high‐grade gliomas, emphasizing the receptors' critical role in the pathophysiology and progression of these tumors due to LDLR's high expression. We delve into LDLR's role in regulating cellular uptake and transport through the brain barrier. Additionally, we highlight LDLR's role in activating several signaling pathways related to tumor proliferation, migration, and invasion, engaging readers with an in‐depth understanding of the molecular mechanisms at play. By synthesizing current research findings, this review underscores the significance of LDLR during tumorigenesis and explores its potential as a therapeutic target for high‐grade gliomas. The collective insights presented here contribute to a deeper appreciation of LDLR's multifaceted roles and implications for physiological and pathological states, opening new avenues for tumor treatment.